A history of Judaism : from its origins to the present - Goodman, Martin, 1953- (Princeton University Press, 2018)
"Judaism is one of the oldest religions in the world, and it has preserved its distinctive identity despite the extraordinarily diverse forms and beliefs it has embodied over the course of more than three millennia ... In this ... book, Martin Goodman takes readers from Judaism's origins in the polytheistic world of the second and first millennia BCE to the temple cult at the time of Jesus. He tells the stories of the rabbis, mystics, and messiahs of the medieval and early modern periods and guides us through the many varieties of Judaism today."--Dust jacket flap